2014
DOI: 10.1097/phm.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Whole-Body Vibration on the Motor Function of Patients with Stroke

Abstract: Whole-body vibration contributed little to improve the functional levels of stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
1
20
0
2
Order By: Relevance
“…Additionally, several studies asserted that WBV training is effective in patients with neurological abnormalities such as cerebral palsy 5 , 6 , 7 ) and multiple sclerosis 8 , 9 ) . A few studies in particular identified WBV training as a feasible intervention for poststroke patients 10 , 11 , 12 , 13 , 14 ) . Van Nes et al observed a short-term effect of WBV on postural control in patients who experienced a hemiplegic chronic stroke 10 ) , and a second study by van Nes et al demonstrated the long-term effect of WBV on balance recovery and activities of daily living in the post-acute phase of stroke 11 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several studies asserted that WBV training is effective in patients with neurological abnormalities such as cerebral palsy 5 , 6 , 7 ) and multiple sclerosis 8 , 9 ) . A few studies in particular identified WBV training as a feasible intervention for poststroke patients 10 , 11 , 12 , 13 , 14 ) . Van Nes et al observed a short-term effect of WBV on postural control in patients who experienced a hemiplegic chronic stroke 10 ) , and a second study by van Nes et al demonstrated the long-term effect of WBV on balance recovery and activities of daily living in the post-acute phase of stroke 11 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The duration of WBV also varied significantly among studies ranging from 30 s to 2.5 min. Moreover, most of the WBV studies planned repeated sessions of WBV ranging from 17 [59] to 30 [61] with the exception of two studies [57,58] who evaluated the effect of a single WBV session. Liao [61] investigated the effect of lowintensity and high-intensity WBV with respect to sham stimulation.…”
Section: Wbv In Chronic Strokementioning
confidence: 99%
“…The outcome variables measured to clarify the possible beneficial effects of WBV included clinical, neurophysiological, and behavioral data. Some authors evaluated the severity of spasticity by means of the Modified Ashworth scale [56,58], others calculated the H/M ratio [58], while some measured balance [59] or muscle strength [54,55,57,60,61]. Outcome measures also included serum level of specific collagen proteins [56] or ultrasound evaluation of muscle structure [59].…”
Section: Wbv In Chronic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…The investigators of randomized controlled trials designed to examine the effects of WBV in post-stroke populations mainly used vertical WBV programs (37, 47) spanning 6-8 weeks (9, 28, 37, 47, 63); the study subjects mostly underwent vibration 3 times a week (37,47,63) at frequencies of 20-50 Hz (37,47,59,63). Patients with chronic stroke (onset ≥ 6 months) and with mild to moderate disability were qualified for the investigations (9, 37, 40, 47).…”
Section: Nervous System Diseasesmentioning
confidence: 99%